2016
DOI: 10.1111/ele.12567
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soil heat on reassembly of bacterial communities in the rhizosphere microbiome and plant disease suppression

Abstract: The rhizosphere microbiome offers a range of ecosystem services to the plant, including nutrient acquisition and tolerance to (a)biotic stress. Here, analysing the data by Mendes et al. (2011), we show that short heat disturbances (50 or 80 °C, 1 h) of a soil suppressive to the root pathogenic fungus Rhizoctonia solani caused significant increase in alpha diversity of the rhizobacterial community and led to partial or complete loss of disease protection. A reassembly model is proposed where bacterial families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(81 citation statements)
references
References 45 publications
5
62
0
1
Order By: Relevance
“…The analysis identified members of the Sphingobacteriaceae, Sphingomonadaceae, and Cytophagaceae among rhizobacteria that responded to the presence of pathogens by upregulation of stress-related genes. A follow-up study by van der Voort et al (2016) used heat treatment of soil to examine the contribution of different rhizobacterial taxa to the suppression of R. solani. The authors suggested that different Actinobacteria, including members of the Streptomycetaceae and Mycobacteriaceae, may contribute to the disease protection since their decrease coincided with the loss of pathogen suppression.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis identified members of the Sphingobacteriaceae, Sphingomonadaceae, and Cytophagaceae among rhizobacteria that responded to the presence of pathogens by upregulation of stress-related genes. A follow-up study by van der Voort et al (2016) used heat treatment of soil to examine the contribution of different rhizobacterial taxa to the suppression of R. solani. The authors suggested that different Actinobacteria, including members of the Streptomycetaceae and Mycobacteriaceae, may contribute to the disease protection since their decrease coincided with the loss of pathogen suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in evenness indicates shifts in microbial species dominance, and evenness has been found to decrease in the rhizosphere with added disturbance (van der Voort et al, 2016). An increase in beta diversity in response to stress may indicate a destabilized microbiome in mammals (Moeller et al, 2013;Zaneveld et al, 2017) with the host being unable to regulate its microbiome.…”
Section: Stressors Decrease the Stability And Increase Beta Diversitymentioning
confidence: 99%
“…(Semi-) natural grasslands are characterized by a high plant species richness (up to 89 species per m 2 (Wilson et al 2012)), containing both monocots and dicots. Interestingly, these plant communities are not static: many plant species show high spatiotemporal dynamics, changing positions within the grassland and fluctuating in abundance over time (Herben et al 1993;Van der Maarel and Sykes 1993). It has been proposed that soil-borne fungal pathogens play an important role in this spatiotemporal species turnover (Olff et al 2000).…”
Section: Introductionmentioning
confidence: 99%